2011
DOI: 10.1016/j.yjmcc.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-rich calcium binding protein: The new regulator of sarcoplasmic reticulum calcium cycling

Abstract: The histidine-rich calcium binding protein (HRC) is a novel regulator of sarcoplasmic reticulum (SR) Ca 2+ -uptake, storage and release. Residing in the SR lumen, HRC binds Ca 2+ with high capacity but low affinity. In vitro phosphorylation of HRC affects ryanodine affinity of the ryanodine receptor (RyR), suggesting a functional role of HRC on SR Ca 2+ -release. Indeed, acute HRC overexpression in isolated rodent cardiomyocytes decreases Ca 2+ -induced Ca 2+ -release, increases SR Ca 2+ -load, and impairs con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 75 publications
1
67
1
Order By: Relevance
“…It regulates sarcoplasmic reticulum (SR) Ca 2+ -uptake, storage and release through calcium pumps and calcium channels [7, 8]. To examine the underlying mechanism of the increased [Ca 2+ ] i induced by HRC in HCC cells, we detected the expression of SERCA2, ryanodine receptor (RyR) and NCX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It regulates sarcoplasmic reticulum (SR) Ca 2+ -uptake, storage and release through calcium pumps and calcium channels [7, 8]. To examine the underlying mechanism of the increased [Ca 2+ ] i induced by HRC in HCC cells, we detected the expression of SERCA2, ryanodine receptor (RyR) and NCX.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations demonstrated that the histidine-rich Ca 2+ -binding protein (HRC) is located in the lumen of the sarcoplasmic reticulum (SR) in heart, which functioned as a new regulator of SR Ca 2+ -homeostasis [7]. Since the discovery of HRC, related studies were all focused on heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins also contribute to this process, including triadin and junctin, which regulate RYR2, and phospholamban, which regulates SERCA2a (4, 5). In the past decade, the histidine-rich Ca-binding protein (HRC) has been suggested to be an additional component of the SR Ca handling machinery (6). HRC is a regulator of both SERCA2a, through its direct binding interaction, and RyR2 function, through its binding to triadin.…”
mentioning
confidence: 99%
“…HRC is a regulator of both SERCA2a, through its direct binding interaction, and RyR2 function, through its binding to triadin. HRC therefore mediates SR Ca storage, uptake, and release (6).…”
mentioning
confidence: 99%
“…Overexpression of a constitutively active inhibitor-1 (I-1c) has beneficial effects on cardiac apoptosis and heart failure progression induced by prolonged beta-adrenergic stimulation [32]. The PRN is also regulated by Heat Shock Protein 20 (Hsp20) and Histidine Rich Calcium Binding protein (HRC) [33,34]. The Hsp20 increases phosphorylation of PLN and sarcoplasmic reticulum calcium cycling, maintains myocyte functioning, and increases cell survival.…”
Section: Central Concept Of Heart Failure Under Systems Biology Perspmentioning
confidence: 99%